1977
DOI: 10.1073/pnas.74.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Surface localization of sites of reduction of nitroxide spin-labeled molecules in mitochondria.

Abstract: The relative rates of reduction of several spin-labeled molecules that partition differently across the hydrophobic-interface of inner membranes from rat liver mitochondria were investigated. Spin labels localized either deep in the hydrophobic region or in the aqueous phase are only slowly reduced; however, a spin-labeled analogue of the cationic detergent cetyltrimethylammonium bromide that partitions at the interface is rapidly reduced by coupled electron transport. Chemical studies on the reduction and oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…To examine its reduction at the mitochondria, methoxycarbonyl-PROXYL was mixed with the mitochondrial fraction. Two segments of the electron transport chain are primarily responsible for the reduction of nitroxyl radicals, complex I and complex II (Chen et al, 1988;Quintanilha and Packer, 1977). Only a small signal decay appeared when glutamate/malate was used, as a substrate for complex I, in both the hemispheres, whereas the addition of succinic acid, as a substrate for complex II, resulted in the clear decay of the methoxycarbonyl-PROXYL ESR signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine its reduction at the mitochondria, methoxycarbonyl-PROXYL was mixed with the mitochondrial fraction. Two segments of the electron transport chain are primarily responsible for the reduction of nitroxyl radicals, complex I and complex II (Chen et al, 1988;Quintanilha and Packer, 1977). Only a small signal decay appeared when glutamate/malate was used, as a substrate for complex I, in both the hemispheres, whereas the addition of succinic acid, as a substrate for complex II, resulted in the clear decay of the methoxycarbonyl-PROXYL ESR signal.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione also affects the reduction of nitroxyl radicals indirectly (Bobko et al, 2007), through their interaction between ascorbic acid and GSH as a redox couple (Mehlhorn, 1991;Meister, 1994;Winkler et al, 1994). In addition, nitroxyl radicals can be reduced enzymatically by complexes I and II in the electron transport chain of the mitochondria (Chen et al, 1988;Quintanilha and Packer, 1977). In this study, we used the nitroxyl radicals to investigate whether the level of antioxidants or the activity of redox enzymes is altered in the brain after ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Because the active, paramagnetic nitroxide is readily reduced to the nonparamagnetic hydroxylamine (which cannot be detected with ESR), spin labels can also be used to probe redox reactions. The depths of sites of oxidation and reduction in the bilayer of mitochondrial membranes have been determined using spin labels (8).…”
mentioning
confidence: 99%
“…It has been reported that microsomes (11), mitochondria (12), and sulfhydryl-related systems (6) contribute to nitroxyl reduction in a body. Additionally, inhibition experiments with ascorbate oxidase suggested that ascorbic acid is a main cytosolic reducing agent for pyrrolidine nitroxyl radicals in biological systems (10,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The nitroxyl radicals are reduced to their corresponding hydroxylamine in an animal body. Numerous in vivo and in vitro studies have clarified that small-molecule antioxidants such as ascorbic acid and GSH, as well as enzymatic systems, contribute to the reduction (6,(9)(10)(11)(12). This reduction is reversible (13) and enhanced under hypoxic conditions in vivo, as well as in vitro (14,15).…”
Section: Introductionmentioning
confidence: 99%